Victorian soundscapes - Picker, John M., 1970- (Oxford University Press, 2003)
Far from the hushed restraint we associate with the Victorians, their world pulsated with sound. This book shows how, in more ways than one, Victorians were hearing things. John Picker draws upon literary and scientific works to recapture the Victorian sense of aural discovery.